Comparison of components of the Good Behavior Game in a preschool classroom. Issue 1 (23rd September 2018) - Foley, Elizabeth A.; Dozier, Claudia L.; Lessor, Amber L.
Abstract : The Good Behavior Game (GBG) is an effective intervention package for decreasing disruptive behavior in various populations and environments. There is, however, limited research evaluating the GBG with preschoolers. Furthermore, few studies have evaluated the effects of components of the GBG, and of those that have, most have done so only after exposure to the GBG package. We evaluated the effects (a) of the GBG on disruptive behavior of preschoolers during group instruction and (b) the major components of the GBG before and after implementation of the GBG package (c) at both the group and individual level. Results suggest that the GBG package was necessary for decreasing disruptive behavior. However, after exposure to the GBG, a response‐independent contingency was effective for maintaining low levels of disruptive behavior at both the group and individual level.